Integrating Green Affective Values and Materials Selection in Automotive Design: A Preliminary Study - See Junn Wayne; Novita Sakundarini; Chin, Christina May May; Raja Ariffin , Raja Ghazilla; Syed Azmi, Sharifah Nadya (International Journal of Integrated Engineering, 2020)
This paper presents a study on the integrating consumerâ€™s green affective values and material selection in the context of product design, specifically in the automotive design. Green affective values are important element in the design to understand userâ€™s emotion, need and preferences toward the green products. It is extremely important to understand userâ€™s feeling on product to avoid potential market failure. The first impression on product is captivated by the use of materials. It is pointed out that intangible issues such as perceptions and intentions of the designer should take a role in the materials selection activity in product design. However, study on the linkage between green affective values and material selection are rarely found in the literature. Therefore, the objectives of this study are to identify the significant green affective values of the consumers in Malaysia and propose a guideline for automotive designers to incorporate affective values into conceptual design and investigate its linkage on material selection. The guideline includes a technology used to translate the consumerâ€™s eco-feeling and impression of a particular component design with appropriate material selection, in this case is on car steering wheel design.Three surveys were conducted to obtain consumerâ€™s understanding on affective values and the feelings elicited when presented with visual stimuli of the material. Semantic differential scale and factor analysis were used to analyze the results. The responses obtained from the surveys were used to develop an eco-tool, which translates userâ€™s feelings and emotions into material properties and linking them to certain materials they perceived as â€œgreenerâ€. Life Cycle Analysis (LCA) and fuzzy logic were used in developing the material scorecard with regards to environmental profile of design model. The eco-tool was validated by product design experts to understand the usefulness and operability of the guideline. It was found that the tool is easy to navigate and having great potential to help designers on integrating green affective value in design with inclusion of technical aspect and cost into the tool.